2023
DOI: 10.1093/jacamr/dlad085
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol-containing regimens for the treatment of carbapenem-resistant A. baumannii ventilator-associated pneumonia: a propensity-weighted cohort study

Abstract: Background Cefiderocol is a novel β-lactam with activity against carbapenem-resistant Acinetobacter baumannii (CRAB), but its role in CRAB pulmonary infections is controversial due to limited evidence. Objectives To assess the association between cefiderocol-containing regimens treatment and 28-day mortality in carbapenem-resistant A. baumannii ventilator-associated pneumonia (VAP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…This study showed a higher, yet not statistically significant, mortality rate in the cefiderocol group compared to the colistin group (51% vs. 37%, p = 0.130). These results were confirmed in several study and meta-analysis, which reported better outcomes in the specific setting of Carbapenem-Resistant Acinetobacter baumannii infections with cefiderocol [ 17 – 20 ].…”
Section: Discussionsupporting
confidence: 56%
“…This study showed a higher, yet not statistically significant, mortality rate in the cefiderocol group compared to the colistin group (51% vs. 37%, p = 0.130). These results were confirmed in several study and meta-analysis, which reported better outcomes in the specific setting of Carbapenem-Resistant Acinetobacter baumannii infections with cefiderocol [ 17 – 20 ].…”
Section: Discussionsupporting
confidence: 56%
“…While the above two studies [ 33 , 34 ] are the only randomised studies until today, there have been a significant number of studies performed in recent years [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and we present these data in Table 2 . Most of these studies were conducted in Italy and are retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies were conducted in Italy and are retrospective in nature. A total of 744 patients were included in the studies in the table [ 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] that addressed the therapeutic management of VAP and bloodstream carbapenem-resistant A. baumannii (CRAB) infections. When examining the mortality of patients that received a cefiderocol-containing regimen versus a comparator regimen that did not contain cefiderocol, mortality was observed in 152 out of the 367 patients (41.4%) that received cefiderocol versus 247 out of the 430 patients (57.4%) that received a comparator antibiotic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 198 , 199 Cefiderocol, a novel β-lactam with activity against CRAB, has shown promise, although its role in treating pulmonary infections caused by this pathogen remains controversial due to limited evidence. 200 , 201 …”
Section: Treatmentmentioning
confidence: 99%